Treatment of giant cell granuloma with intralesional corticosteroid injections: a case report - Bayar, Ozlem Filiz (J Istanb Univ Fac Dent, 2015)
Giant cell granuloma is rare in the head and neck region and most commonly affects the maxilla and mandible. Giant cell granulomas are benign but occasionally aggressive lesions that are traditionally treated with surgery. Because it is a benign process, less radical and non-surgical treatment alternatives are required. Corticosteroid injection is a viable alternative in the treatment of central giant cell granuloma to avoid surgery. We aim to present a case which was successfully treated with intralesional corticosteroid injection in the maxilla.